(untitled) (The Review of Diabetic Studies, 2024)
Background: Decisions about initiating or withdrawing life‑sustaining treatment often occur when patients lack capacity, placing multidisciplinary teams and families in ethically charged situations. Recent studies reveal persistent gaps in core competencies, shared decision‑making, and organisational support, with physicians dominating decisions and nurses having limited influence. Cultural and spiritual norms, communication barriers, and resource constraints further complicate the process. Aim: To synthesise evidence published between 2020 and 2024 on ethical challenges and solutions in end‑of‑life decision‑making within multidisciplinary healthcare teams. Method: A descriptive systematic review was conducted in accordance with established guidelines. 5 databases (PubMed, CINAHL, Embase, PsycINFO, and Scopus) were searched for English‑language studies. 13 studies meeting the inclusion criteria were analysed and quality‑appraised. Results: Six themes emerged. Hierarchical dynamics prevailed, with decisions often made by physicians while nurses were marginalised. Cultural and organisational influences—such as collectivist values, spiritual beliefs, and unclear palliative care concepts—delayed discussions or discouraged participation. Communication and collaboration varied; some teams shared information but lacked structured joint decision‑making mechanisms. Moral sensitivity and training influenced clinicians’ confidence and advocacy. Structured frameworks, such as decision‑staging and ethics committees, improved clarity and family engagement, while resource shortages during crises intensified ethical conflicts. Conclusion: End‑of‑life decision‑making remains dominated by hierarchical cultures, inadequate communication, and varying cultural norms. Empowering non‑physician voices, improving moral sensitivity through training, adopting structured decision-making frameworks, and tailoring strategies to cultural contexts are vital for aligning care with patients’ values and reducing moral distress.